Continuing education for the public secondary school library personnel in the Division of Quezon City a follow-up study - Quinto, Mae Lyn P. (1998)
The study determined the perceived continuing education needs of secondary public school library personnel in the Division of Schools of Quezon City. Specifically, it aimed to identify the library personnel's educational background, constraints involved in attending continuing education programs, the continuing education programs in the last fourteen years; and lastly, to find out if the recommendations of Ms. Elizabeth Bautista were implemented.